2021
DOI: 10.1002/ces2.10100
|View full text |Cite
|
Sign up to set email alerts
|

Pore‐forming process in dehydration of metakaolin‐based geopolymer

Abstract: The geopolymer catalyst supports utilized in the nuclear waste containers for the Fukushima Daiichi Nuclear Power Station, will be required to have high porosity, and durability. This work presents the synthesis of a potassium and metakaolin based geopolymer and its performance upon dehydration. During water content measurements of the samples, it was seen that in the demolded samples, the water content quickly decreased to less than 30% within 7 days, while the samples, that had the cap removed from the conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…However, rapid generation of initial gels can make products cover the surface of remnant precursor particles. Moreover, the samples with a lower water/binder ratio have less water, which will weaken the free movement of ions and retard the bond linkage [ 47 ]. Therefore, the duration from the strength of the initial setting to the strength of the final setting is prolonged, and the reduction of the final setting time is not as much as the initial setting time.…”
Section: Resultsmentioning
confidence: 99%
“…However, rapid generation of initial gels can make products cover the surface of remnant precursor particles. Moreover, the samples with a lower water/binder ratio have less water, which will weaken the free movement of ions and retard the bond linkage [ 47 ]. Therefore, the duration from the strength of the initial setting to the strength of the final setting is prolonged, and the reduction of the final setting time is not as much as the initial setting time.…”
Section: Resultsmentioning
confidence: 99%
“…29) The porosity and pore distribution of geopolymers play an important role in the application of catalyst supports. Previous research 21) showed that macropores may be formed in the first 4 d. In the present work, potassium and metakaolin-based geopolymer samples were synthesized. The workflow was carried out by evaluating the mechanical strength value and pore size distribution of the geopolymer, which are based on two factors, the varying early-age curing time and air tightness after early-age curing.…”
Section: Introductionmentioning
confidence: 91%
“…5,[17][18][19][20] Consequently, geopolymers have been developed as candidate materials for hydrogen recombination catalyst support in previous research. 2,21) The mechanical strength of geopolymers is strongly affected by the content of K 2 O and the water coefficient of H 2 O/metakaolin, while the compressive strength value of the sample is not significantly different from the SiO 2 to K 2 O molar ratio variable. 22) When a sample is cured at a high temperature, compared to one cured at room temperature, the higher curing temperature will increase the early compressive and flexural strength, and even reach the target value within 1 d. In addition, the effect of temperature depends on the curing time.…”
Section: Introductionmentioning
confidence: 99%